(untitled) (Health Renaissance, 2011)
Halitosis means an unpleasant odor of the expired air, regardless of the source of this odor. The foul breath originating from the oral cavity itself is termed as oral malodor and it is usually the main contributor of unpleasant breath in an otherwise healthy individual. The most predominant causes of halitosis are gingivitis, periodontitis, and tongue coating. However, several non-oral pathologic conditions have also been related to halitosis, including infection of the upper and lower respiratory tracts, the gastrointestinal tract, and some metabolic diseases involving the kidneys and the liver, which should never be overlooked. Though this complaint of bad breath has existed from time immemorial, it has only recently come to scientific platforms of analysis and is being increasingly recognized as a social stigma in an ever-growing sensitive society. Breath malodor has important socio-economic consequences. Literature reveals almost 1 billion a year is spent in the United States on deodorant-type mouth rinses and mints which provide only short-term masking effects, instead of spending the money on a proper diagnosis and etiologic care to manage bad breath. Sulfur containing volatiles are the main constituent of oral malodor and that their levels correlate with the intensity as determined organoleptically. The treatment of intraoral halitosis consists of scaling/root planing and daily removal of tongue coating, and for extraoral halitosis, treatment of underlying systemic disease by a specialist. Keywords: halitosis; bad breath; oral malodour DOI: http://dx.doi.org/10.3126/hren.v9i2.4983 Health Renaissance 2011: Vol.9 (No.2): 106-111